“Les sphères divisées”. D’Aristophane à Ibn Hazm - Ben Slama, Raja (Anales del Seminario de Historia de la Filosofía, 2002)
The author makes a study of the problem of love understood as meeting of the two parts of a soul-sphere. It is a Greek myth that has had a long tradition in the Arabic literature on love. The author is centered in Ibn Hazm of Cordoba.